A hypercrosslinking-induced self-assembly strategy for preparation of advanced hierarchical porous polymers with customizable functional components. Issue 38 (26th April 2017) - Xu, Hongji; Wu, Jinlun; Zheng, Bingna; Mai, Weicong; Xu, Fei; Chen, Luyi; Liu, Hao; Fu, Ruowen; Wu, Dingcai; Matyjaszewski, Krzysztof
Abstract : Advanced hierarchical porous polymers with customizable functional components were synthesized by development of a facile and efficient hypercrosslinking-induced self-assembly strategy. Abstract : The fabrication of advanced hierarchical porous polymers with a unique 3D nanonetwork structure composed of functional core–microporous shell nanoparticles was reported based on the development of a simple and efficient hypercrosslinking-induced self-assembly strategy.